Christelike gesindheid in die werkplek in Suid-Afrika vandag - Voster, JM (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The topic of labour ethics has been researched in Christian ethics on many occasions within the various Christian traditions. However the context of labour constantly shifts and labour ethics should from time to time be revisited form a Christian perspective. South Africa experiences such a shift in the current process of social transition. The year 2005 was characterised by labour unrest, while unemployment, affirmative action and emigration of expertise are still highly debated issues. This article focuses on this changing context and addresses these issues from the perspective of Christian attitude. Christian attitude is to embody the attitude of Christ namely compassion, stewardship, service and obedience to God. By applying these norms in the field of labour, Christian ethics may give direction to employers and employees in dealing with the changing context.